The Hidden Reasons for the Defeat of the Red Army in Galicia and Volyn in June-July 1941 (Bulletin of Kharkiv National University of Internal Affairs, 2025)
One of the most tragic and difficult to comprehend pages in the history of World War II is the defeat of the Southwestern Front of the Red Army in September 1941. This article attempts to explain why the largest Soviet military group, which was equal in size to Army Group South and had superiority in tanks, aircraft and artillery, suffered crushing defeats in Galicia and Volhynia. Understanding the underlying causes of these events and assessing them comprehensively is important for contemporary historiography. One of the key hidden factors behind the Red Army’s catastrophic defeats in Ukraine in the summer of 1941 was the shortage of personnel and the de-intellectualisation of the command structure, which led to a significant decline in the level of strategic leadership.It has been established that Soviet troops were insufficiently prepared for the realities of modern mechanised warfare – motorised warfare. Inefficient use of equipment, lack of interaction between units, poor coordination of actions, misjudgement of the operational situation and lack of strategic vision led to massive losses of personnel and equipment. A comparison with the Wehrmacht showed a significant professional advantage of the German command staff, who had in-depth special training and combat experience in modern warfare.In contrast, Soviet units were mainly led by individuals without the necessary experience and education: among the senior command, 57.6 % were under 45 years of age, and 75 % had been in their positions for less than a year. The poor professional training of most commanders made the Soviet troops difficult to control. Mistakes in planning and an inability to command large mechanised units led to disorganisation, loss of morale and heavy casualties. Of the 170 divisions of the Southwestern Front (2.9 million people), 28 were completely destroyed, 70 lost more than half of their personnel and equipment, and only 259 of the 4,785 tanks remained in service.